How to save the world in six (not so easy) steps : bringing out the best in nonprofits - Schizer, David M. (Ascent Audio, 2023)
The US has over 1.5 million nonprofits, which touch our lives in countless ways. The finest are inspiring, but unfortunately, too many let us down. Luckily, there's a solution. How to Save the World in Six (Not So Easy) Steps by expert scholar and nonprofit leader David M. Schizer is the ultimate management book for nonprofit professionals, board members, and donors. Nonprofits need to do two challenging things really well: figure out the best way to advance the mission, and then build support for it. With entertaining anecdotes from his many years leading Columbia Law School and international humanitarian organization JDC, as well as interviews with an all-star cast of nonprofit leaders, Schizer explains how to accomplish these twin goals: Plan: Run a rigorous planning process; Persevere: Line up internal support; Prioritize: Set priorities by asking three key questions; Pivot: Test innovations; Publicize: Share ideas and hold yourself accountable; and Partner: Raise more money by involving donors in the work. By chronicling the good, the bad, and the ugly at nonprofits and explaining how to get more out of them, this book shows how we can "save the world" together with the "six Ps.".